Real‐world outcomes of chemoradiotherapy for unresectable Stage III non‐small cell lung cancer: The SOLUTION study. (30th July 2020) - Horinouchi, Hidehito; Atagi, Shinji; Oizumi, Satoshi; Ohashi, Kadoaki; Kato, Tomohiro; Kozuki, Toshiyuki; Seike, Masahiro; Sone, Takashi; Sobue, Tomotaka; Tokito, Takaaki; Harada, Hideyuki; Maeda, Tadashi; et al.
Abstract: There are limited real‐world data on the treatment practices, outcomes, and safety of chemoradiotherapy (CRT) alone in potential candidates for immune checkpoint inhibitors (ICI) for unresectable non‐small cell lung cancer (NSCLC). In this study, we analyzed the safety and efficacy of CRT in patients who underwent CRT and would satisfy the key eligibility criteria for maintenance therapy with durvalumab (eg, no progression after CRT) in real‐world settings (m‐sub) for unresectable Stage III NSCLC between 1 January 2013 and 31 December 2015 at 12 sites in Japan. The m‐sub comprised 214 patients with a median follow‐up of 31.6 months (range 1.9‐65.8 months). Median overall survival (OS) and progression‐free survival (PFS) from completing CRT were 36.4 months (95% confidence interval [CI] 28.1 months to not reached) and 9.5 months (95% CI 7.7‐11.7 months), respectively. Consolidation chemotherapy did not influence OS or PFS. Median PFS was 16.9 vs 9.1 months in patients with vs without epidermal growth factor receptor ( EGFR ) mutations, with PFS rates of ~20% at 3‐4 years. Pneumonitis was the most common adverse event (according to MedDRA version 21.0J), and about half of events were grade 1. Pneumonitis mostly occurred 10‐24 weeks after starting CRT, peaking at 18‐20 weeks. Esophagitis and dermatitis generally occurred from 0 to 4 weeks, peaking at 2‐4 weeks after starting CRT. Pericarditis was rare and occurred sporadically. In conclusion, the results of the m‐sub provide real‐world insight into the outcomes of CRT, and will be useful for future evaluations of ICI maintenance therapy after CRT. Abstract : We analyzed the efficacy and safety of chemoradiotherapy (CRT) for unresectable Stage III non‐small cell lung cancer in patients who would satisfy the key eligibility criteria for maintenance therapy with durvalumab (eg, no progression after CRT) in real‐world settings (m‐sub). Our results provide real‐world insight into the outcomes of CRT, and will be useful for future evaluations of immune checkpoint inhibitor (ICI) maintenance therapy after CRT.